“Ubah Laku” Model through Corporate Social Responsibility: Case Study of PT Asri Dharma Sejahtera - Firmansyah, Muchammad Resya; Purnamasari, Dian Indri; Prasetio, Januar Eko (International Journal Labs, 2023)
This study aims to examine in depth the “Ubah Laku” CSR model applied by PT Asri Dharma Sejahtera (ADS), identify and analyze the level of sustainability and impact of the aforementioned CSR program run by ADS on the local community, and identify the success or failure factors of the program implemented, along with the obstacles encountered. Qualitative research methods were chosen as an approach in this study. The object of this research is PT Asri Dharma Sejahtera (ADS), a Regional Owned Enterprise (BUMD) of Bojonegoro Regency. Based on factual observations made by researchers at ADS, it can be concluded that the company has made efforts in implementing sustainable Corporate Social Responsibility CSR programs. In addition, the results from this research can also provide an overview for other companies on how to implement CSR effectively and sustainably.